Analisis Faktor Bahaya Kesehatan Kerja Dan Potensi Penyakit Akibat Kerja Di PT. X - Sheila Aldri Ananda; Adinda Putri Santoso; Nico Linggi Pongmasangka (Akademi Keperawatan Yarsi Samarinda, 2026)
The manufacturing industry faces a high risk of work-related illnesses (WRI), which reduce productivity. This descriptive observational study aims to identify occupational health hazards at PT X Cikarang, analyze the potential for WRI (Presidential Regulation No. 7/2019), and evaluate the compliance of control measures with occupational safety and health (OSH) regulations. Data were collected from March to May 2025 through production area observations, interviews with the SHE team, and document reviews. The study identified four main hazard factors: physical (noise and temperature), chemical (welding fumes), ergonomic (repetitive movements and awkward postures), and psychosocial (night shift systems and production targets). These factors have the potential to trigger occupational health and safety issues such as Noise-Induced Hearing Loss (NIHL), reduced lung function, Musculoskeletal Disorders (MSDs), and chronic fatigue. In general, PT X has complied with Law No. 1/1970 and Minister of Manpower Regulation No. 5/2018 through periodic workplace monitoring, the provision of PPE, and specialized health examinations (audiometry and spirometry). However, the implementation of SMK3 (Government Regulation No. 50/2012) has not been optimal because the company has not yet been formally certified and has not conducted a comprehensive ergonomic evaluation. It is concluded that OSH control at PT X is already functioning well, but requires strengthening in the ergonomic assessment of workstations and the acceleration of SMK3 certification. Keywords: occupational health hazards, occupational disease, automotive manufacturing, NIHL, ergonomics.